Między stłumieniem a autentycznością. Metafora Don Carlosa w filmie Leontine Sagan Dziewczęta w mundurkach - Mazur, Daria (Przestrzenie Teorii, 2019)
Mazur Daria, Między stłumieniem a autentycznością. Metafora Don Carlosa w filmie Leontine Sagan Dziewczęta w mundurkach [Between Suppression and Authenticity. The Metaphor of Don Carlos in Leontine Sagan’s Movie Mädchen in Uniform]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 143–166. ISSN 1644-6763. DOI 10.14746/pt.2019.32.7. The article is a comprehensive analysis of the intertextual references to Frederick Schiller’s tragedy Don Carlos in Leontine Sagan’s movie Girls in Uniform (Mädchen in Uniform, 1931). The author considers the complex circumstances of the cooperation between the director and the artistic director, Carl Froelich, during the production. Moreover, she also presents the literary basis for the movie, namely the tragedy by Christy Winsloe (Gestern und Heute – Yesterday and Today). On this basis, the author analyses the multilevel presence of two phenomena in the movie: suppression and authenticity, which are related to the metaphor of Don Carlos and the plot of love between two women. The contexts for the analysis are inspired by research in the anthropology of romanticism, psychoanalysis, the psychology of sexual identity, and research on the works of Frederick Schiller.